Retinopathy Due to Anemia: Doi: 10.36351/pjo.v40i4.1747 - Bodla, M Afzal; Maria Afzal Bodla; Syedah, Nalain (Pakistan Journal of Ophthalmology, 2024)
Anemia-related retinopathy is a common condition, often asymptomatic and discovered incidentally during routine evaluations. A comprehensive, multidisciplinary approach is essential to ensure that even unusual presentations result in positive outcomes, preventing further morbidities and their long-term consequences. We present the case of a 22-year-old woman who reported a rapid decline in vision and sought care at Bodla Eye Care in Multan. She had only one functional eye (right), with the left eye affected by phthisis bulbi. Her best-corrected visual acuity in the right eye was limited to light perception.